A palaeomagnetic study of Syrian volcanic rocks of Miocene to Holocene age - A. L. Abdeldayem; D. H. Tarling; J. M. Abou-Deeb; M. M. Otaki (Geofísica Internacional, 1999)
Miocene and younger volcanic rocks from Syria show both normal and reversed polarities after thermal demagnetisation. Similarities in site mean directions may be used to establish lavas erupted at similar times. The observed polarities suggest that some Quaternary volcanics are older than previously mapped. The site mean directions of reversed and intermediate polarity sites are more scattered than for normal polarity sites, and the overall scatter is larger than would be expected from models of secular variation simulated by westward or eastward drift of the present non axial dipole field. The normal sites are also twice as strongly magnetised as the reversed and intermediate polarity sites. The mean direction of the Quaternary sites is consistent with an axial geocentric dipole model, but the Miocene sites, while having antipodal directions for the two polarities, have a mean inclination that is shallower than the axial dipole field and may indicate persistent geomagnetic effects or possibly regional tilting.